GIZ’s evaluation system - and GIZ Evaluation Unit (GIZ GmbH, 2018)
This provides a general description of GIZ’s new evaluation system, which is designed to implement our new policy and to achieve the objectives of evaluation reform. This general description is accompanied by two other documents that provide supplementary details of GIZ’s key evaluation instruments: project evaluations for BMZ business and corporate strategic evaluations. They are geared in particular to GIZ staff members who commission, implement or support evaluations and to evaluators who conduct evaluations on behalf of GIZ as well as repre-sentatives of commissioning parties, clients and cooperation partners. The current versions are very much a ‘work in progress’ in many regards. We are well aware that we will only be able to meet our own high expectations of our evaluations if we continue to develop their quality in dialogue with project staff, our commissioning parties, clients and partners and with evaluation practitioners and experts from the academic, scientific and research community. We look forward to taking on this task and to sharing our experience with all interested parties.